RNA-Seq Analysis Revealed circRNAs and Genes Associated with Abdominal Fat Deposition in Ducks - Yunfeng Yang; Chunyan Yang; Zhong Zhuang; Jiaming Mao; Anqi Chen; Tingting Zhou; Hao Bai; Yong Jiang; Guobin Chang; Zhixiu Wang (Animals, 2024)
Fat deposition is an important factor affecting meat quality and feed conversion efficiency in meat ducks. This study aims to identify key circRNAs and genes affecting abdominal fat deposition. The correlations between abdominal fat and other growth performances were analyzed in 304 F2 generation of Cherry Valley duck Runzhou Crested White ducks, and an RNA-seq analysis of abdominal fat tissues from ducks with high and low rates of abdominal fat was performed. Growth performance results showed that Abdominal fat ratio and Intramuscular fat were significantly higher in the high rates of abdominal fat (HF)group than in the low rates of abdominal fat (LF) group for ducks. RNA-seq analysis of abdominal fat tissue unveiled 85 upregulated and 72 downregulated circRNAs among the differentially expressed ones. Notably, 74 circRNAs displayed more than four-fold differential expression, constituting 47.13% of the differentially expressed genes. Functional enrichment analysis of the differentially expressed circRNA source and target genes indicated that 17 circRNAs might partake in regulating duck abdominal fat production by influencing pathways like PPAR signaling, lipid droplets, and triglyceride metabolism. Lastly, multiple circRNA-microRNA-messenger RNA interaction networks were constructed. The results of this study establish the groundwork for understanding the molecular mechanisms that regulate abdominal fat deposition in ducks, offering a theoretical reference for the selective breeding of high-quality meat-producing ducks.